Associations of single and multiple vitamin levels with pediatric oral mucosal diseases: a cross-sectional study with multi-model analysis - Fang, Panpan; Wang, Yingyuan; Chen, Nan; Gao, Kaijie; Yang, Liu; Wang, Xuchen; Li, Ci; Sun, Qianqian; Li, Tiewei; Yang, Junmei (Frontiers in Nutrition, 2025)
BackgroundVitamins play a crucial role in children’s oral health, yet the associations between multiple vitamins and pediatric oral mucosal diseases (OMDs) remain unclear. Existing studies often focus on single vitamin, leaving gaps in understanding the complex interactions of vitamin mixtures on OMDs and age-specific effects.MethodsThis cross-sectional study included 1,287 children from the Children’s Hospital Affiliated to Zhengzhou University (January 2022 to April 2025), comprising 167 OMDs patients and 1,120 healthy controls. Participants were stratified into early childhood (0–6 years; n = 665) and school-age (6–12 years; n = 622) groups. Serum levels of vitamins A, D, E, C, B6, and B9 were measured. Individual and mixture effects on OMDs were assessed using multivariable logistic regression, quantile g-computation (qgComp), and Bayesian kernel machine regression (BKMR), with age-stratified analyses.ResultsOur analyses consistently revealed a significant inverse association between vitamin mixtures and OMDs prevalence across all age groups (p < 0.05). Vitamins D, E, and B6 were significantly lower in OMDs patients versus controls (all p < 0.001). All models confirmed a protective association between vitamin B6 and OMDs risk. BKMR further identified a U-shaped relationship: moderate concentrations were protective, while higher levels increased risk. Quartile analysis supported this trend, with strongest protection at mid-range concentrations (Q3: OR = 0.27, 95%CI 0.15–0.45; P for trend <0.001).ConclusionThis study reveals that vitamin mixtures reduce OMDs risk in children. Vitamin B6 exhibited a U-shaped relationship, protective at moderate levels. Age-specific effects were observed: vitamin E inversely and vitamin B9 positively associated with OMDs exclusively in early childhood.